In Search of Safe Harbors - Privacy and Surveillance of Refugees in Europe - Kift, Paula (AoIR Selected Papers of Internet Research, 2016)
Over the course of 2015, more than a million refugees and migrants arrived at the borders of Europe. One of the ways in which the European Union (EU) attempted to manage the continuous inflow of people was through the collection of vast amounts of personal information; information that is not only used to assess and process asylum claims but also to prevent irregular migration and to alleviate national security concerns. This paper addresses two questions: How do the EU’s information collection practices impact asylum seekers’ data protection, privacy and fundamental rights? And what can these practices teach us about the field of information privacy law and the nature of transborder data flows more generally?In order to address these questions the paper will outline the different kinds of information that the EU collects about asylum seekers, how that information is collected, and for what purpose. The paper will focus in particular on the legal and normative challenges raised by two specific EU regulations, namely EUROSUR (drone and satellite surveillance of the Mediterranean Sea) and Eurodac (biometric information collection at the border). In so doing, the paper also provides important insights about the field of information privacy law and the regulation of transborder data flows more generally, including the distinction between the right to data protection and the right to privacy; the inadequacy of defining anonymity as non-identifiability; and the risks and harms associated with outsourcing information collection practices to both third countries and private parties.